Diagnosis and Surgical Treatment of Complicated Forms of Cardiac Myxoma - Volodymyr V. Isaienko; Maryna M. Serdiuk; Volodymyr F. Onishchenko; Andrii G. Goriachev; Tetiana I. Dedkova; Rostyslav M. Vitovskyi (Ukrainian Journal of Cardiovascular Surgery, 2024)
Of all benign neoplasms of the heart, cardiac myxomas (CM) are found in 50-90% of cases. National Amosov Institute of Cardiovascular Surgery of the National Academy of Medical Sciences of Ukraine has experience in surgical treatment of 968 heart tumors. Of these, CM was observed in 868 cases.The aim. To conduct an analysis of the frequency of detection of complicated forms of CM, to present the causes and methods of diagnosis and surgical treatment of these complications.Material and methods. Pathology of the valvular apparatus combined with CM occurred in 70 (8.1%) patients: an isolated lesion of the mitral valve (MV) was observed in 27 (38.6%) patients, concomitant relative insufficiency of the tricuspid valve (TV) was found in 10 (14.3%) cases.Results. During the surgical treatment of valvular pathology, we performed valve replacement in 15 (21.4%) patients (MV in 12, TV in 1, aortic valve [AV] in 1, AV + MV in 1 patient), reconstructive operations with a positive functional effect in 50 (71.4%) patients, and isolated tumor removal from the valve apparatus in 5 (7.1%) cases.Relapses after surgical treatment of CM in our cohort of patients occurred in 1.8% cases. Among patients with sporadic myxomas of the heart, recurrence was observed in 13 cases (1.5%). If the principle of radical removal of CM followed, relapses occurred in 1.3% (10 cases out of 772). In 7 cases of myxoma syndrome, the recurrence rate was 42.5%.Embolic complications of the course of CM were determined in 58 (6.7%) cases. Damage to cerebral vessels was found in 46 (77.9%), embolisms of peripheral vessels in 10 (16.9%), and embolisms of coronary arteries in 2 (5.1%) patients. In 41 patients with CM (4.2%), a significant lesion of the coronary arteries was found, which required surgical intervention. To correct the pathology of the coronary vessels, the following was performed: stenting in 3 cases (7.3%), coronary bypass surgery in 35 (85.4%), dissection of the muscle bridge that narrowed left anterior descending artery in 2 (4.9%), left ventricular aneurysm plastic surgery in 1 case (2.4%).Conclusions. Calcium changes in left atrial myxoma were most often accompanied by mechanical damage to the leaflets and chordal apparatus of the mitral valve. Hyperthermia was a frequent manifestation of CM (56.8%). In isolated cases, the temperature reaction may be associated with the tumor infection process.